The Metasomatized Mantle beneath the North Atlantic Craton: Insights from Peridotite Xenoliths of the Chidliak Kimberlite Province (NE Canada). (7th January 2020) - Kopylova, M G; Tso, E; Ma, F; Liu, J; Pearson, D G
Abstract: We studied the petrography, mineralogy, thermobarometry and whole-rock chemistry of 120 peridotite and pyroxenite xenoliths collected from the 156–138 Ma Chidliak kimberlite province (Southern Baffin Island). Xenoliths from pipes CH-1, -6, -7 and -44 are divided into two garnet-bearing series, dunites–harzburgites–lherzolites and wehrlites–olivine pyroxenites. Both series show widely varying textures, from coarse to sheared, and textures of late formation of garnet and clinopyroxene. Some samples from the lherzolite series may contain spinel, whereas wehrlites may contain ilmenite. In CH-6, rare coarse samples of the lherzolite and wehrlite series were derived from P = 2·8 to 5·6 GPa, whereas predominant sheared and coarse samples of the lherzolite series coexist at P = 5·6–7·5 GPa. Kimberlites CH-1, -7, -44 sample mainly the deeper mantle, at P = 5·0–7·5 GPa, represented by coarse and sheared lherzolite and wehrlite series. The bulk of the pressure–temperature arrays defines a thermal state compatible with 35–39 mW m –2 surface heat flow, but a significant thermal disequilibrium was evident in the large isobaric thermal scatter, especially at depth, and in the low thermal gradients uncharacteristic of conduction. The whole-rock Si and Mg contents of the Chidliak xenoliths and their mineral chemistry reflect initial high levels of melt depletion typical of cratonic mantle and subsequent refertilization in Ca and Al. Unlike the more orthopyroxene-rich mantle of many other cratons, the Chidliak mantle is rich (∼83 vol%) in forsteritic olivine. We assign this to silicate–carbonate metasomatism, which triggered wehrlitization of the mantle. The Chidliak mantle resembles the Greenlandic part of the North Atlantic Craton, suggesting the former contiguous nature of their lithosphere before subsequent rifting into separate continental fragments. Another, more recent type of mantle metasomatism, which affected the Chidliak mantle, is characterized by elevated Ti in pyroxenes and garnet typical of all rock types from CH-1, -7 and -44. These metasomatic samples are largely absent from the CH-6 xenolith suite. The Ti imprint is most intense in xenoliths derived from depths equivalent to 5·5–6·5 GPa where it is associated with higher strain, the presence of sheared samples of the lherzolite series and higher temperatures varying isobarically by up to 200 °C. The horizontal scale of the thermal-metasomatic imprint is more ambiguous and could be as regional as tens of kilometers or as local as <1 km. The time-scale of this metasomatism relates to a conductive length-scale and could be as short as <1 Myr, shortly predating kimberlite formation. A complex protracted metasomatic history of the North Atlantic Craton reconstructed from Chidliak xenoliths matches emplacement patterns of deep CO2 -rich and Ti-rich magmatism around the Labrador Sea prior to the craton rifting. The metasomatism may have played a pivotal role in thinning the North Atlantic Craton lithosphere adjacent to the Labrador Sea from ∼240 km in the Jurassic to ∼65 km in the Paleogene.